Keys to understanding the interdependence between organizational culture and institutional performance: The case of the educational institution Fe y Alegría N° 02 - Trujillo, Christian (2019)
Although an extensive national and international bibliography has been produced to explain the success of educational management in the I.E. Fe y Alegría, the different approaches about it have omitted a historical analysis of the influence of the organizational development process on performative aspects, such as institutional performance. Considering this premise, the case of the I.E. Fe y Alegría N ° 02, with its experience, allows us to answer the following question: in what way did the transformations, that occurred in the organizational culture between the years 1980 and 2017, influence current institutional performance? The evidence shows that there is a complex process called «mythification of rules and profiles». This process, even though it has not yet been explored in depth in the literature, has repercussions on its institutional management system, legitimizes the taking of actions and authority inside the educational campus, and coexists in parallel with a phenomenon of technical and institutional coupling. Finally, it is concluded that this educational establishment is a space of resistance against the influence of organizational premises of the business world; despite rationally using limited resources in a precarious context.